Digital screening tool for the assessment of cognitive impairment in unsupervised setting - DigiDEM-SCREEN: Study protocol for a validation study - Zeiler, Michael; Dietzel, Nikolas; Kammerer, Klaus; Frick, Ulrich; Pryss, Rüdiger; Heuschmann, Peter; Prokosch, Hans-Ulrich; Grässel, Elmar; Kolominsky-Rabas, Peter (BMJ Open, 2025)
Introduction Dementia is one of the most relevant widespread diseases, with a prevalence of currently 55 million people with dementia worldwide. However, about 60-75% of people with dementia have not yet received a formal diagnosis. Asymptomatic screening of cognitive impairments using neuropsychiatric tests has been proven to efficiently enhance diagnosis rates. Digital screening tools, in particular, provide the advantage of being accessible without spatial or time restrictions. The study aims to validate a digital cognitive screening test (digiDEM-SCREEN) as an app in the German language. Methods and analysis This is a multicentre study in Bavaria. Participants are people with mild cognitive impairment, people with dementia in an early stage and cognitively healthy people. Recruitment will take place in specialised diagnostic facilities (memory outpatient clinics). 135 participants are aimed based on a power analysis. Sociodemographic data, diagnosis and results of neuropsychiatric tests (Consortium to Establish a Registry for Alzheimer's Disease, Montreal Cognitive Assessment, digiDEM-SCREEN) will be collected at one point per person via electronic data capturing. The sensitivity, specificity and corresponding cut-off values will be determined based on receiver-operating-characteristic curves. The correlation of the digiDEM-SCREEN test with existing cognitive screening/testing procedures will be analysed. Ethics and dissemination The study obtained ethical approval from the Ethics Committee of the Julius-Maximilians-Universität of Würzburg (JMU) (application number: 177/23-sc). The test will give feedback about the current cognitive status and possible cognitive impairments that should lead to the users seeking further diagnostic measures by medical professionals. It will be accessible free of charge in established app stores. The results of the validation study will be published in peer-reviewed journals.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chronic Disease; Cognition; Dementia; eHealth; GERIATRIC MEDICINE